Studi Karakteristik Tailing Pada Lokasi Eks Penambangan Timah di Bukit Sambung Giri Kecamatan Merawang Kabupaten Bangka - Irvani Irvani; Elsha Delvi Artasari (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2018)
Tailing deposits at the ex-tin mining area in Bangka and Belitung Island has a large number of economical residual minerals. This study is to identify tailing characteristic and its potential mineralogy and elements based on shallow hand boring (Auger) samples, along streamline in the west part of Sambung Giri Hill. Every coordinate sample plotted on the base map. Laboratory analysis using Stereo Microscope for identifying mineral characteristics, and geochemical analysis using XRF for identification of the presence of elements. The tailing deposits has laterally grain size gradation to downstream, composed above 94% sand fraction, and a small amount of shale and granule fraction. Quartz mineral presence more than 90%, followed by iron oxide (hematite), clay, zircon, cassiterite, ilmenite, monazite and tourmaline minerals, showed low consistency in lateral spatial except quartz, with its Rare Earth Elementh (REE) composition is Cerium (Ce), Lanthanum (La), Yttrium (Y), Neodymium (Nd) and Samarium (Sm).